Conventional Character Empowerment: A Critical Study On Students' Environmental Care Character Profile at Noemuti State High School - Yunawati Sele; Made Santiari (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
In the learning process, properly empowering students' environmental care character is a crucial endeavor. This study was conducted to analyze the effectiveness of empowering students' environmental care character, as measured by the environmental care character profile. This quantitative descriptive study used a student environmental care character questionnaire instrument. The results showed that the average value of students' environmental care character was 64.34, which was in the sufficient category. Out of the 52 participants in this study, only 14.29 demonstrated an average level of environmental care character in the good category. Other respondents, specifically 77.55 % and 8.16 %, had average values in the sufficient and less categories. This shows that the conventional approach has not been effective in empowering students' environmental care character. Other efforts are needed, namely 1) school commitment to integrate character values into the school's vision and mission including the implementation of various school activities, 2) teacher commitment to select, develop and implement learning models that provide opportunities for students to be actively involved in learning, for example problem-based learning models, project-based learning models, contextual learning models and outdoor learning, 3) Development and use of ICT-based media and learning resources that are integrated with environmental literacy and 4) increasing the involvement of relevant stakeholders such as parents, government and the community in efforts to empower students' environmentally conscious character